2004
DOI: 10.1677/jme.1.01563
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin potentiates insulin-stimulated leptin expression and release from differentiated brown adipocytes

Abstract: The pituitary hormone prolactin (PRL) exerts pleiotropic effects, which are mediated by a membrane receptor (PRLR) present in numerous cell types including adipocytes. Brown adipose tissue (BAT) expresses uncoupling proteins (UCPs), involved in thermogenesis, but also secretes leptin, a key hormone involved in the control of body weight. To investigate PRL effects on BAT, we used the T37i brown adipose cell line, and demonstrated that PRLRs are expressed as a function of cell differentiation. Addition of PRL l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 45 publications
0
23
1
Order By: Relevance
“…In mouse adipocytes, PRL alone has no effect on leptin release but it inhibits the insulin-induced production of leptin [33]. Conversely, when combined with insulin, PRL increases leptin release from brown adipocytes, which contradicts the higher concentration of leptin in brown adipose tissue in PRL receptor-deficient mice [34]. The present study showed that serum leptin levels did not differ with PRL treatment among diabetic groups.…”
Section: Discussioncontrasting
confidence: 66%
“…In mouse adipocytes, PRL alone has no effect on leptin release but it inhibits the insulin-induced production of leptin [33]. Conversely, when combined with insulin, PRL increases leptin release from brown adipocytes, which contradicts the higher concentration of leptin in brown adipose tissue in PRL receptor-deficient mice [34]. The present study showed that serum leptin levels did not differ with PRL treatment among diabetic groups.…”
Section: Discussioncontrasting
confidence: 66%
“…The cross talk between prolactin and insulin signaling pathway in brown adipocytes demonstrated that prolactin potentiates insulin-stimulated secretion of leptin by brown adipose tissue (Viengchareun et al, 2004). In PCOS patients with hyperprolactinemia other causes must be investigated because hyperprolactinemia is not a clinical manifestation of PCOS (Filno et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…169 resistin, 170 leptin 171 and adiponectin 172 are produced by fat during pregnancy in mice. Prl receptor signaling can regulate adipokine expression, 173,174,175 suggesting the possibility that while the mouse placenta is not the direct source of all metabolic hormones, unlike humans, it may still orchestrate the network. The best evidence in mice that placental hormones regulate fetal growth is that of the pleckstrin homology-like domain, family A member 2 gene which regulates the fetal growth by influencing the number of endocrine cells in the placenta.…”
Section: Review Of Placental Development and Function In The Contementioning
confidence: 99%